(untitled) (IMC Journal of Medical Science, 2020)
Background and objectives: Several types of Burkholderia pseudomallei antigens have been used to determine the antibody response in acute and asymptomatic cases. In the present study, we have detected immunoglobulin G (IgG) antibody to recombinant truncated flagellin antigen (RTFA) of B. pseudomallei in the sera of acute melioidosis cases and healthy individuals from melioidosis endemic areas of Bangladesh by indirect enzyme-linked immunosorbent assay (ELISA). In parallel, IgG antibody to sonicated whole cell antigen (SWCA) of B. pseudomallei was determined to compare with anti-RTFA antibody. Methodology: Serum samples from culture confirmed melioidosis cases and from healthy individuals aged 21 years and above residing in melioidosis endemic rural areas were included in the study. Serum IgG antibody to RTFA and SWCA of B. pseudomallei was determined by indirect ELISA. Results: Out of 8 culture confirmed acute melioidosis cases, 7 (87.5%) and 8 (100%) were positive for anti-B. pseudomallei IgG antibodies by RTFA and SWCA methods respectively. Among 361 healthy individuals, the rate of seropositivity by RTFA-ELISA was significantly less than that of SWCA-ELISA (16.1% versus 26.8%; p = 0.001). The mean optical density (OD) of RTFA-ELISA of positive cases was significantly less than that of SWCA-ELISA in both melioidosis and healthy individuals (0.79±0.11 versus 2.4±0.08, p = 0.0001; 0.67±0.01 versus 1.27±0.02, p = 0.0001). The sensitivity and specificity of RTFA-ELISA were 88.9% and 100% respectively. Conclusion: Findings of the study suggest that multiple or combination of antigens should be used to study the seroprevalence of B. pseudomallei infection in a community. Also, prospective study is necessary to find out the duration of persistence of antibodies to different antigenic components of B. pseudomallei after exposure. Ibrahim Med. Coll. J. 2020; 14(1): 47-52